Long QT in stunned myocardium: unrecognised cause of acquired long QT syndrome (Journal of Medical Science, 2014)
Long QT syndrome (LQTS) is a heart disorder characterized by a prolongation of the QT interval on ECG and a predisposition to ventricular tachyarrhythmias, which may lead to syncope, cardiac arrest or sudden cardiac death. This condition may be inherited or induced by external factors such as drugs, electrolyte imbalances and some acquired cardiac diseases. The review addresses LQTS caused by acute cardiac illnesses which are associated with a large amount of stunned myocardium, i.e. the reperfused myocardial infarction and the group of stress-related cardiomyopathies. In these cases, specific ECG evolutionary changes may be observed, i.e. dynamic deep T-wave inversion and QT interval prolongation which predispose to fatal polymorphic ventricular tachyarrhythmia, i.e. torsade de pointes. However, lethal arrhythmias are relatively rare in these instances and probably concern patients with an underlying predisposition to LQTS. The pathological mechanisms of both repolarization abnormalities and ventricular arrhythmias as well as the practical approach how to interpret electrocardiographic changes and identify high risk patients are discussed in this review.